Detoxification of aflatoxin B1 by a Bacillus subtilis spore coat protein through formation of the main metabolites AFQ1 and epi-AFQ1 - Subagia, Raditya; Schweiger, Wolfgang; Kunz-Vekiru, Elisavet; Wolfsberger, Dominik; Schatzmayr, Gerd; Ribitsch, Doris; Guebitz, Georg M. (Frontiers in Microbiology, 2024)
A variety of important agricultural crops host fungi from the Aspergillus genus can produce cancerogenic secondary metabolites such as aflatoxins. Consequently, novel strategies for detoxification and their removal from food and feed chains are required. Here, detoxification of Aflatoxin B1 (AFB1) by the Bacillus subtilis multi-copper oxidase CotA (BsCotA) was investigated. This laccase was recombinantly produced in E. coli while codon optimization led to duplication of the amount of active protein obtained. CuCl2 was added to the cultivation medium leading to a 25-fold increase of Vmax corresponding to improved incorporation of Cu 2+ into the enzyme protein which is essential for the catalytic reaction. To avoid potential cytotoxicity of Cu 2+ , cultivation was performed at microaerobic conditions indeed leading to 100x more functional protein when compared to standard aerobic conditions. This was indicated by an increase of Vmax from 0.30 ± 0.02 to 33.56 ± 2.02 U/mg. Degradation kinetics of AFB1 using HPLC with fluorescence detection (HPLC-FLD analysis indicated a theoretical substrate saturation above solubility in water. At a relatively high concentration of 500 µg /L, AFB1 was decomposed at 10.75 µg/Lh (0.17 nmol*min -1 *mg -1 ) at a dosage of 0.2 µM BsCotA. AFQ1 and epi-AFQ1 were identified as the initial oxidation products according to mass spectrometry (i.e. HPLC-MS, HPLC-QTOF). None of these molecules were substrates for laccase but both decomposed in buffer. However, decomposition does not seem to be due to hydration of the vinyl ether in the terminal furan ring. Genotoxicity of the formed AFB1 was assessed in several dilutions based on the de-repression of the bacterial SOS response to DNA damage indicating about 80-times reduction in toxicity when compared to AFQ1. The results of this study indicate that BsCotA has high potential for the biological detoxification of aflatoxin B1.